Implementasi Modul Water Quality Meter pada Komunitas Petani Udang Vaname Jawa Timur - Firnanda Pristiana Nurmaida; Agus Indra Gunawan; Teguh Hady Ariwibowo; Ferry Ariyanto; Utari Sanaba; Muhamad Aldino Habibulloh; Orlando Pratama Tambunan; Muhammad Wafiq Kamaluddin (Universitas Nurul Jadid, 2024)
Vannamei shrimp is one of the leading commodities in fisheries aquaculture, due to its competitive price and the ability to be mass-produced with high stocking densities. Many coastal communities in East Java capitalize on this opportunity by engaging in vannamei shrimp cultivation. However, most shrimp farmers still measure pond water quality using conventional methods and record water quality parameters on paper, which is highly inefficient. With this issue in mind, the author sought to engage in community service by inviting representatives from the East Java vannamei shrimp farming community. The method involved delivering lectures and interactive discussions with shrimp farmers to understand their perceptions and insights regarding pond water quality, followed by the handover of modules, and subsequently evaluating the modules' usage by the shrimp farmers. As a result of this community service, we introduced a tool to assist traditional shrimp pond farmers in monitoring water quality, in the form of a